Magneto-optical properties of two – layer film systems based on Fe and Pt - Bezdidko, O.V.; Shkurdoda, Yu.O.; Vashchenko, S.M. (Physics and Chemistry of Solid State, 2021)
The paper shows the experimental results of the study of magneto - optical properties and phase composition of thin films and multilayers based on Fe and Pt. Samples were obtained in a high-vacuum chamber (10–8 Pa) by layer-by-layer deposition from pots at room temperature. It has been shown that FCC solid solution of FePt is formed already in the process of deposition on the substrate (sital plates). Depending on the concentration of the atoms of the components in the unannealed samples, three phases can be formed: (i) s.s. Fe(Pt); (ii) Fe3Pt; (iii) FePt. The first sign of the beginning of ordering in the FCC phase of FePt should be considered the appearance of superreflections in the form of lines (001) and (002) during heat treatment. Depending on the total thickness of the multilayer or individual layers, the annealing temperature at which extrareflexes appear can vary in the range of 300–570 K. All the samples obtained have a low coercivity (0.25 - 0.4 mT). Magneto-optical studies have shown that an increase in the content of the non-magnetic component decreases the main magnetic characteristics. However, In [Fe(3)/Pt(3)]n/S multilayers with the number of repeatable elements from 2 to 8 an increase in the main magnetic parameters is observed compared with bilayer films at the same effective thickness.